Strategies for diagnosis, control, and prevention of mastitis (2009)
In Colombia, the great diversity in management, methods of milking and breeds for milk production, makes very difficult to unify the rules for mastitis control; therefore the veterinarian’s job, according to the available resources in each herd is to advise the best procedures for both, milking routines and mastitis control. Influenced by the differences in management, the prevalence of each of the microorganisms that may cause mastitis varies from region to region and even from herd to herd within the same area. As a rule of thumb, the more basic the system, the less practices for mastitis control are present; this situation consequently leads to a high presentation of contagious mastitis by Streptococcus agalactiae. As the management improves, and dry cow therapy practices are implemented particularly in systems with milking machines, the mayor pathogen isolated is Staphylococcus aureus which is a regular resident in the skin. The number of cases caused by environmental microorganisms is very low, but maintains the clinical level of serious acute mastitis reported in dairy herds in other countries. Due to the indiscriminate and sometimes inappropriate use of antibiotics used for mastitis treatment, a high level of resistance to antibiotics has resulted to most of the antibiotics already in the market. It is imperative a close cooperation between the organizations for drug regulation and control, the pharmaceutical industry and the Veterinary medical profession to established rules and standards to safeguard this non-renewable resource.